ADHD in children and young people: prevalence, care pathways & service provision - Sayal, Kapil; Prasad, Vibhore; Daley, David; Ford, Tamsin; Coghill, David (Lancet, 2017)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a common childhood behavioural disorder – systematic reviews indicate that the community prevalence of ADHD globally is between 2% to 7%, with an average of around 5%. In addition, a further 5% of children have significant difficulties with over-activity, inattention and impulsivity that are just sub-threshold to meet full diagnostic criteria for ADHD. Estimates of the administrative (clinically diagnosed and/or recorded) prevalence vary worldwide and although increasing over time, ADHD is still relatively under-recognised and under-diagnosed in most countries, particularly in girls and older children. ADHD often persists into adulthood and is a risk factor for other mental health disorders and negative outcomes including educational under-achievement, difficulties with employment and relationships, and criminality. The timely recognition and treatment of children with ADHD-type difficulties provides an opportunity to improve their long-term outcomes. This review includes a systematic review of the community and administrative prevalence of ADHD in children and adolescents; an overview of the barriers to accessing care for ADHD; a description of costs associated with ADHD; and a broad discussion of evidence-based pathways for the delivery of clinical care, including a focus on key issues for two specific age groups - pre-school children and adolescents requiring transition of care from child to adult services.